The importance of iodine nutrition during pregnancy - clinical aspect - Žabková, Kristýna; Krátký, Jan; Jiskra, Jan; Vítková, Hana (Casopis lekaru ceskych, 2021)
Iodine is an essential constituent of thyroid hormones. Thyroid hormones regulate brain development, growth and metabolism of the human body. Inadequately low iodine intake and decreased thyroid hormone synthesis can lead to iodine deficiency disorders. The severity of disorders depends not only on the degree of iodine deficiency, but also on the stage of the human development. Many areas of the world, including the Czech Republic, have been affected by natural iodine deficiency and the incidence of iodine deficiency disorders has been historically high. Fortification of food-grade salt was an effective step towards reduction of iodine deficiency impact. Although the Czech Republic has been considered to be an iodine sufficient area since 2004, iodine deficiency is still a threat to subgroups of population with an increased demand for iodine, such as pregnant women and newborns. Moreover, these groups are particularly sensitive to even mild iodine deficiency, because it could permanently affect the cognitive development of the fetus and have a negative effect on the course of pregnancy. Conversely, in other groups of the population steps taken to prevent iodine deficiency diseases may lead to excessive iodine intake with potential risks. It is necessary to control the iodine fortification and regularly monitor the iodine status of the population considering the individual risk groups.
Keywords: fyziologie výživy v těhotenství; Thyroid-stimulating hormone; Female; novorozenec; hypothyroidism; pregnancy; těhotenství; Česká republika; autoimmune thyroiditis; ženské pohlaví; Czech Republic; thyroid gland; Hypothyroidism; Pregnancy; Prenatal Nutritional Physiological Phenomena; Iodine; lidé; Humans; thyroid hormone; iodine; jod; hyperthyroidism; thyroid peroxidase antibodies; Infant, Newborn